2013
DOI: 10.1186/1752-1947-7-78
|View full text |Cite
|
Sign up to set email alerts
|

Brugada syndrome in a family with a high mortality rate: a case report

Abstract: IntroductionBrugada syndrome is a hereditary arrhythmia characterized by a specific electrocardiographic pattern and an increased risk of sudden cardiac death, with an apparent absence of structural abnormalities or ischemic heart disease. To date, mutations in the sodium channel, voltage-gated, type V, alpha subunit gene and glycerol-3-phosphate dehydrogenase 1-like gene are estimated to account for approximately 28% of Brugada syndrome probands.Case presentationWe report the case of a 32-year-old mixed-race … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
1
Order By: Relevance
“…However, the brother's ECG indicated a conduction delay, which could contribute to BrS in terms of the depolarization hypothesis, and special observation would be considered for him. Family members who carry BrS-associated variants but remain asymptomatic and have normal ECGs indicate that genetic studies are of limited usefulness for determining risk (28). In contrast, even though family gene variants are not determined, there is no reason to exclude BrS if the patients exhibit the Brugada ECG pattern.…”
Section: Discussionmentioning
confidence: 99%
“…However, the brother's ECG indicated a conduction delay, which could contribute to BrS in terms of the depolarization hypothesis, and special observation would be considered for him. Family members who carry BrS-associated variants but remain asymptomatic and have normal ECGs indicate that genetic studies are of limited usefulness for determining risk (28). In contrast, even though family gene variants are not determined, there is no reason to exclude BrS if the patients exhibit the Brugada ECG pattern.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Em contrapartida, não temos conhecimento de estudos que demonstrem a prevalência do padrão eletrocardiográfico de Brugada na população brasileira; apenas relatos de casos e um estudo de prevalência familiar de SB. [28][29][30][31] A prevalência encontrada neste estudo é inferior aos dados relatados na literatura e pode estar relacionada à baixa prevalência de padrão eletrocardiográfico de Brugada na população brasileira. Por ser a SB um quadro genético, é possível que as variações genéticas encontradas na população estudada possam ter influenciado a prevalência desse padrão eletrocardiográfico.…”
Section: Discussionunclassified
“…Another study [ 36 ] showed that the GPD1-L mutation itself causes a loss function of enzymatic activity, and decreased GPD1-L activity would have then increased the substrate G3P, and fed the PKC-mediated phosphorylation of SCN5A at S1503 where such phosphorylation was known to decrease I Na . A study showed that GPD1-L gene accounted for 11%–12% BrS probands [ 37 ], but other studies showed no identification on any missense GPD1-L gene mutation, suggesting that GPD1-L may not be a major cause of BrS [ 38 , 39 ]. Further studies are needed to obtain the accurate prevalence of GPD1-L variants in BrS.…”
Section: Genetic Factors Of Brsmentioning
confidence: 99%